DEMOGRAFIC AND THE RURAL DEVELOPMENT OF ONE COSTAL-MOUNTAINOUS-BORDER REGION AND NEW DEVELOPMENT PATEIS - Milanović, Milan R. (Economics of Agriculture, 2006)
This unique example of not just rural development but general development are gathered in municipality Herceg Novi (235 km², 27 places, 33.034 inhabitants.), with strongly different agro-ecological areas: form the seaside with intensive agriculture, hilly with fruit production and cattle breeding, sub-mountain areas with low quality pastures, up to the area of woods (above 1000 meters) and to the compact larch woods (1895мнв). Municipality Herceg Novi is not just seaside but also hilly – mountain municipality not only by its natural-geographical contrast and other developing resources. This municipality is also on the boundary with process of deagrarisation and depopulation. On the contrary of all expectations most inhabitants are extremely old with very reported differences in micro level. This is why integral approach is necessary in consideration of multifunctionality and urban planning and especially analytical view of present and future settlements with are already in deep aging. Valorization of agricultural and agro-ecological potentials can be real pillar for their survival.